Impact of exercise pulmonary hypertension on postoperative outcome in primary mitral regurgitation. Issue 5 (17th October 2014) - Magne, Julien; Donal, Erwan; Mahjoub, Haifa; Miltner, Beatrice; Dulgheru, Raluca; Thebault, Christophe; Pierard, Luc A; Pibarot, Philippe; Lancellotti, Patrizio
Abstract : Aims: The management of asymptomatic patients with mitral regurgitation (MR) remains controversial. Exercise-induced pulmonary hypertension (ExPHT) was recently reported as a strong predictor of rapid onset of symptoms. We hypothesised that ExPHT is a predictor of postoperative cardiovascular events in patients with primary MR. Methods and results: One hundred and two patients with primary MR, no or mild symptoms (New York heart association (NYHA) ≤2), and no LV dysfunction/dilatation, were prospectively recruited in 3 centres and underwent exercise-stress echocardiography. The presence of ExPHT was defined as an exercise systolic pulmonary arterial pressure >60 mm Hg. All patients were closely followed up and operated on when indication for surgery was reached. Postoperative events were defined as the occurrence of atrial fibrillation (AF), stroke, cardiac-related hospitalisation or death. Among the 102 patients included, 59 developed ExPHT (58%). These patients were significantly older than those without ExPHT (p=0.01). During a mean postoperative follow-up of 50±23 months, 28 patients (26%) experienced a predefined cardiovascular event. Patients with ExPHT had significantly higher rate of postoperative events (39% vs 12%, p=0.005); the rate of events was still higher in these patients (32% vs 9%, p=0.013), even when excluding early postoperative AF (ie, within 48 h). Event-free survival was significantly lower in the ExPHT group (all events: 5-year: 60±8% vs 88±5%, p=0.007, events without early AF: 5-year: 67±7% vs 90±4%, p=0.02). Using Cox multivariable analysis, ExPHT remained independently associated with higher risk of postoperative events in all models (all p≤0.04). Conclusions: ExPHT is associated with increased risk of adverse cardiac events following mitral valve surgery in patients with primary MR.